The Effect of Interactive Agility Training on Some Motor Abilities and Skill Performance in Soccer Players - Khalaf, Saddam Hussein; Hammadi, Firas Talib (Indonesian Journal Publisher, 2025)
The current study aimed to identify the effect of interactive agility training on developing some motor abilities and skill performance of Al-Hawija Sports Club football players. The researcher used the experimental approach by designing an experimental and control group with pre- and post-tests to suit the research problem and sample. The researcher deliberately selected the research community, which consisted of players from first-division football clubs in Kirkuk Governorate (Al-Hawija Club, North Oil Club) for the 2024-2025 sports season, totaling 52 players. After a lottery, the Al-Hawija Sports Club was chosen to be the research sample, which numbered (26) players. The experimental research sample was then randomly selected (lottery), which numbered (10) players to represent the experimental group from the research community. The control group consisted of (10) players from Al-Hawija Sports Club. (Two) goalkeepers were statistically excluded, as were (4) players for non-compliance and repeated absences. The researcher conducted an exploratory experiment on (4 players) from Al-Huwaija Sports Club were excluded from the research sample. The researcher conducted homogeneity and equivalence procedures between the experimental and control groups. After obtaining the results and processing them statistically, the researcher concluded that the training used according to interactive agility is more effective than traditional training in enhancing the players' motor and skill capabilities. The most important recommendations were: The researcher recommends that trainers use interactive agility training in their training units, given its effectiveness in developing the research variables, as proven by the research results.